Hyperchaos in a second-order discrete memristor-based map model - Bao, Bo-Cheng; Li, Houzhen; Wu, Huagan; Zhang, Xi; Chen, Mo (Electronics letters, 2020)
This Letter presents a new second-order discrete map model, which is derived from a simple sampling switch-based memristor-capacitor circuit. The memristor-based map model has infinite unstable and critical stable fixed points, and exhibits chaotic and hyperchaotic behaviours via a period-doubling bifurcation scenario. These complex dynamical behaviours are confirmed by the phase portraits, iterative sequences and basins of attraction.